Implementasi Pembelajaran berbasis HOTS (Higher Order Thinking Skill) Dalam meningkatkan Kognitif Peserta didik pada Mata Pelajaran Fiqih - Maulida, Kiromatul; Amini, Izzat (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2025)
This research is motivated by the 21st-century learning system, which requires us to respond to the increasingly competitive demands of the times. As society evolves, education becomes more complex to produce competent outputs. Therefore, learning implementation is needed to develop excellent and intelligent human resources, both in general knowledge and religious studies. In this regard, the implementation of HOTS (Higher Order Thinking Skills)-based learning in the fiqh subject for fifth-grade students at MI Nurur Rahmah is expected to enable students to apply their knowledge in daily life activities. The purpose of this study is to examine the implementation of HOTS-based learning in enhancing students' cognitive abilities in the fiqh subject for fifth-grade students at MI Nurur Rahmah. This study employs a qualitative research method with a descriptive approach. The findings reveal that the learning process aligns with cognitive domain stages and incorporates HOTS indicators. This indicates that the implementation of HOTS-based learning in the fiqh subject for fifth-grade students at MI Nurur Rahmah has been successfully carried out.